Comparison of sputum induction with broncho-alveolar lavage in the diagnosis of smear-negative pulmonary tuberculosis - Ganguly, KC; Hiron, MM; Mridha, ZU; Biswas, M; Hassan, MK; Saha, SC; Rahman, MM (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):115-23. The abstract of this article is available on the PubMed website